The Benefits of Online Payment as Perceived by Grade 12 Students of Bestlink College of the Philippines at Novaliches, Quezon City School Year 2021-2022: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Online payment is described in business as a mode of payment in which money is transmitted online via electronic money transfer. Nowadays, online payments are rapidly growing, especially during the COVID-19 Pandemic. Online payment systems include things like online shopping and online banking.  These services are highly significant nowadays because they are convenient, and consumers do not have to leave their homes to make purchases. In keeping with the modernizing society, this research will provide systems that will be critical for students to manage fast transactions and engage with online transactions. This study aimed to determine The Benefits of Online Payment as perceived by Grade 12 Students of Bestlink College of the Philippines School Year 2021-2022. The study explains the different benefits of online payment to the students that can promote flexible thinking and teach students the benefits of online payment for different tasks, especially in this pandemic. The survey is limited to only fifty students who will serve as the respondents for this study via Google Forms. The chosen format that we used for the questionnaire was the Likert scale format. The results of this study make the students knowledgeable about the benefits of using online payment and allow them to learn online payment easily.  The findings suggest that the main benefits of using online payment are cost and time savings, increased sales, and reduced transaction costs. Based on the result, most students strongly agreed that online transaction is more convenient for them. We also conclude that students prefer Gcash when making online payments.
Keywords: Online payment; electronic money transfer; Benefits; Transactions